2021
DOI: 10.3389/fsurg.2021.662720
|View full text |Cite
|
Sign up to set email alerts
|

Revision Hip Arthroscopy in the Native Hip: A Review of Contemporary Evaluation and Treatment Options

Abstract: Hip arthroscopy is a reproducible and efficacious procedure for the treatment of femoroacetabular impingement syndrome (FAIS). Despite this efficacy, clinical failures are observed, clinical entities are challenging to treat, and revision hip arthroscopy may be required. The most common cause of symptom recurrence after a hip arthroscopy that leads to a revision arthroscopy is residual cam morphology as a result of inadequate femoral osteochondroplasty and restoration of head–neck offset, though several other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, studies have shown that an elevated LCEA has been observed to be associated with risk of requiring revision surgery. 18,21 Femoral head extrusion index indicates the percentage of uncovered femoral head, with a normal range of 17%-27%. 20 The mean values of extrusion index of participants in PHT were within the normal range prior to the interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies have shown that an elevated LCEA has been observed to be associated with risk of requiring revision surgery. 18,21 Femoral head extrusion index indicates the percentage of uncovered femoral head, with a normal range of 17%-27%. 20 The mean values of extrusion index of participants in PHT were within the normal range prior to the interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This brought the mean LCEA of participants who underwent arthroscopic surgery closer to the normal range, indicating that arthroscopic surgery reduces over‐coverage. However, studies have shown that an elevated LCEA has been observed to be associated with risk of requiring revision surgery 18,21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, revision surgery is difficult due to trauma, high cost, and postoperative complications and will further increase the risk of further revision, resulting in a vicious cycle. Preventing and curing aseptic loosening of artificial joints is a great challenge in orthopedics [4][5][6].…”
Section: Introductionmentioning
confidence: 99%